Translator’s Creativity found in the Process of Japanese-Korean Translation - Cho, Sang-Eun (Meta, 2006)
AbstractIt has been commonly understood (in Korea) that Japanese and Korean’s linguistic similarities make Japanese-Korean translation easier than translations from other languages into Korean. However, this does not concur with the fact that Japanese-Korean translations are not better compared to other language combinations from the readers’ point of view. This might be due to the problem of translationese caused by language interference, but the present research zooms in on translator’s ‘creativity’ and observes the effects of translator’s creativity on translation quality. The method of research involves analyzing transcriptions gathered through Think Aloud Protocol (TAP) from thirteen professional translators for the purpose of evaluating the strategies used by the translators and examining the occurrence of shift. The research confirms that Japanese-Korean translator creativity is restricted, and such result demonstrates the need for scholars and educators in translation education to recognize and appreciate the concept of creativity and to devise new educational approaches for nurturing creativity.